Relawan Siap Siaga Pemutus Rantai Penyebaran Covid-19 Desa Sukonatar - Erina Tresnayanti; Ermita Yusida (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this activity is to break the chain of spread of the Covid-19 virus through a team of volunteers who are on standby. In the activities of the team carrying out the covid-19 prevention program, namely spraying disinfectants in village areas, giving an appeal to the importance of maintaining cleanliness, distributing social assistance and BLT to residents who have an impact on Covid-19. With these activities, it can provide benefits to the community so that they can continue to carry out their daily lives. The results of the activity showed that while being a volunteer for the Covid-19 virus in Sukonatar Village, starting from the distribution of social assistance and BLT, routine spraying of disinfectants, distribution of masks to people affected by Covid-19 greatly helped the community in dealing with the pandemic.